EMPATHY IN EARLY CHILDHOOD:A PRELIMINARY STUDY - Charyna Ayu Rizkiyanti; Ade Irva Murty (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
Nowadays, bullying is still becoming an unsolvable issue in Indonesia. Among students, bullying phenomenon happens started from kindergarten level untill high school level. By having empathy, children are being much more understanding, more adept at handling anger and daring to say no to commit violence, including bullying. This current research examines the preschoolers’ empathy through self-report in response to short clip. The short clip assesses the extent to which children endorsed behaviours that were regarded as showing their empathy towards others (cognitive and affective). A total of 50 preschoolers with age 4-6 year old participated in this study. By decriptive analysis, result found that all preschoolers with the exception of a few showed empathy in two components, both cognitive and affective. This study implies that in order to elevate children’s empathy, parents must be modelling how to identify and express emotions toward them. Saat ini, intimidasi masih menjadi masalah yang tidak dapat diselesaikan di Indonesia. Di kalangan siswa, fenomena bullying terjadi mulai dari tingkat TK hingga tingkat SMA. Dengan memiliki empati, anak-anak menjadi jauh lebih pengertian, lebih mahir dalam menangani kemarahan dan berani mengatakan tidak untuk melakukan kekerasan, termasuk bullying. Penelitian saat ini meneliti empati anak-anak prasekolah melalui laporan diri sebagai tanggapan terhadap klip singkat. Klip pendek menilai sejauh mana anak-anak mendukung perilaku yang dianggap menunjukkan empati mereka terhadap orang lain (kognitif dan afektif). Sebanyak 50 anak prasekolah dengan usia 4-6 tahun berpartisipasi dalam penelitian ini. Dengan analisis deskriptif, hasil menemukan bahwa semua anak prasekolah dengan pengecualian beberapa menunjukkan empati dalam dua komponen, baik kognitif dan afektif. Studi ini menyiratkan bahwa untuk meningkatkan empati anak, orang tua harus menjadi model bagaimana mengidentifikasi dan mengekspresikan emosi terhadap mereka.Keywords: Empathy, preschooler, cognitive-affective empathy, compassionate